APPLICATION OF EXPONENTIAL SMOOTHING METHOD TO FORECASE THE AMOUNT OF RICE PRODUCTION IN TANATE RIAJA DISTRICT, BARRU REGENCY - Khalilah Nurfadilah; Adnan Sauddin; Winda Saputri (University of Mataram, 2022)
Exponential smoothing is a forecasting method with data that tends to fluctuate. Rice production is one of the data with these properties. This study discusses the agricultural production, the variable used to predict the level of rice production in Tanete Rilau District, Barru Regency . This study aims to predict the total production of rice plants from 2021 to 2025. The analysis results show that the forecast values for the entire production of rice plants from 2021 to 2025 are 24016.6, 24613.14, 25018.36, 25342.54, and 25601.88, respectively. It can be seen that rice production forecasting using the exponential smoothing method fluctuates yearly.